Special Issue on Pesticide Applications in Agricultural Systems - Giuseppe Manetto; Emanuele Cerruto; Domenico Longo; Rita Papa (Applied Sciences, 2021)
The European Directive 2009/128/EC on the Sustainable Use of Pesticides recognizes the use of Plant Protection Products (PPP) as having great impact on human health and the environment [...]